A PORTRAIT OF PROFESSIONAL EFL TEACHERS AT SENIOR HIGH SCHOOL - Nisaul Qomariyah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: EFL teachers are considered to be professional in their fields. Becoming a professional EFL teacher needs to possess several competencies to support his or her teaching. Regarding to the teachers’ competencies, the subjects whose being investigated in this research met the criteria of pedagogical and professional competence. It is found that the subject A and subject B had their own way and differentiation in achieving their pedagogical and professional competence. Both of subjects had a good personality, it means by having good personality leads them into the professionalism. Subject A is a professional teacher from the aspect of having good personality, social, and have a good sense of humor, and subject B also professional from the term of improving her self-development in teaching. One thing stands out from the results of this research that whatever the condition or where they live and teach, the professional teachers have one thing in common: they are professional in the real sense of word. This research analyzed qualitatively with a case study as the design. The data gathered in-depth investigation from the online interview, spreading self-reflection form, and did the data analysis.Keywords: EFL Teachers, professional Teachers, teachers' competencies